Rotational Surfaces In Isotropic Spaces Satisfying Weingarten Conditions - Ogrenmis, Alper Osman (Sciendo, 2016)
In this paper, we study the rotational surfaces in the isotropic 3-space I-3 satisfying Weingarten conditions in terms of the relative curvature K (analogue of the Gaussian curvature) and the isotropic mean curvature H. In particular, we classify such surfaces of linear Weingarten type in I-3.
Keywords: Isotropic space; rotational surface; Weingarten surface